1974
DOI: 10.1073/pnas.71.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Complementarity of Yeast Glycoprotein Mating Factors

Abstract: Cell fusion between opposite mating types 5 and 21 of the yeast Hansenula wingei is initiated by a strong sexual agglutination reaction. The mating factors responsible for the specificity of cellular recognition are complementary glycoproteins which form a physical complex in vitro. The complex is assayed by recovery of agglutination activity of the multivalent 5-factor after the univalent 21-factor has been inactivated by treatment of the complex with alkali. The 5-factor 21-factor complex, purified on Sephar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1975
1975
1994
1994

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…1975, HAGIYA et al 1977, purified, and found to be glycoproteins , HAGIYA 1980. Furthermore, molecular complexes of the released agglutination substances have been demonstrated in both yeasts (CRANDALL et al 1974. This is strong evidence to support the ligand hypothesis of sexual agglutination.…”
supporting
confidence: 69%
“…1975, HAGIYA et al 1977, purified, and found to be glycoproteins , HAGIYA 1980. Furthermore, molecular complexes of the released agglutination substances have been demonstrated in both yeasts (CRANDALL et al 1974. This is strong evidence to support the ligand hypothesis of sexual agglutination.…”
supporting
confidence: 69%
“…FIG. 6. Mating tube formation in M-919 cells by supplement of a factor, the culture fluid of the mating tube-formed M-1057.…”
Section: Discussionmentioning
confidence: 99%
“…Intermolecular complexes of agglutinins from opposite mating types have been observed in H. wingei, S. kluyveri, and S. cerevisiae (14,16,28,67), indicating that the agglutinins interact directly with each other, i.e., that the agglutinins are involved in complementary interactions. The nature and properties of the interactive bonds in complexes of purified agglutinins are similar to those of cell-cell bonds formed between intact cells (9, 89, 116).…”
Section: Agglutinin Bindingmentioning
confidence: 99%